MANAJEMEN SEKOLAH DAN MADRASAH - Ayu Nur Chamidah; Sri Minarti (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Education is the main pillar in the development of a nation. To achieve the goal of quality education, effective and efficient management is required. School management includes a series of activities such as planning, organizing, implementing and controlling educational resources to achieve predetermined goals. Similarly, madrasah as an Islamic educational institution has special characteristics that combine general and religious knowledge. The implementation of School-Based Management (SBM) or Madrasah-Based Management (MBM) is an important strategy in decentralizing education. Therefore, an in-depth study of school and madrasah management is needed to identify existing problems and formulate appropriate solutions to improve the quality of education in Indonesia